Urinary incontinence in men - Skierkowska, Natalia; Kujawska, Agnieszka; Husejko, Jakub; Gajos, Małgorzata; Prylińska, Monika; Topka, Weronika; Kożuchowski, Marcin; Wysocka, Oktawia; Kędziora-Kornatowska, Kornelia; Androsiuk-Perkowska, Joanna; et al. (Journal of Education, Health and Sport, 2018)
Background: Urinary incontinence is one of the most common problems among older people. The number of men struggling with incontinence is also gradually increasing. The lifestyle of the urinary incontinence, including low physical activity, poor eating habits, and nicotinic have a big influence on the occurrence of urinary incontinence. Urinary incontinence is associated with poor quality of life, social isolation and depression. Material and methods: Analysis of articles in the Google Scholar and PubMed database using keywords: urinary incontinence, risk factors of urinary incontinence, symptoms of urinary incontinence, men, treatment. Results: The incidence of urinary incontinence increases more than five times in men over 65 years of age. The problem may be exacerbated by respiratory, circulatory, muscular and neurological diseases. Men are often ashamed of problems with incontinence and rarely report to the doctor, which causes the problem to get worse and often requires the use of invasive methods of treatment. Conclusions: The incidence of urinary incontinence among men increases with age. Currently, methods that effectively cure urinary incontinence among men are poorly understood, therefore it is necessary to conduct further research among people with this problem. Broader education of the elderly will allow to some extent eliminate risk factors and reduce the number of people struggling with the problem of urinary incontinence.